2010
DOI: 10.1177/0884533610361605
|View full text |Cite
|
Sign up to set email alerts
|

Early vs Delayed Enteral Nutrition in Critically Ill Medical Patients

Abstract: This study was conducted to identify current practice in provision of enteral nutrition (EN) and to determine effects of early enteral nutrition (EEN) on length of stay in the medical intensive care unit (ICU). In this prospective, observational study, medical ICU patients were evaluated to determine their candidacy for EEN. If patients were candidates for EN and expected to remain nothing-by-mouth for 48 hours, they were classified as receiving EEN (within 24 hours of admission) or delayed EN. Thirty-six pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 20 publications
5
25
0
1
Order By: Relevance
“…Often, hospitalized elderly patients who are nutritionally depleted develop pneumonia leading to respiratory failure [25, 26]. When patients have impaired underlying lung function and suffer from infections such as pneumonia, they fail to oxygenate the blood properly, leading to respiratory failure and the need for mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Often, hospitalized elderly patients who are nutritionally depleted develop pneumonia leading to respiratory failure [25, 26]. When patients have impaired underlying lung function and suffer from infections such as pneumonia, they fail to oxygenate the blood properly, leading to respiratory failure and the need for mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no difference in overall mortality between those who received early and late enteral feeding, there was an excess mortality in those with aspiration pneumonia. Previous studies have shown that early enteral feeding can reduce mortality [22] and incidence of sepsis [3], hasten recovery [23] and shorten length of hospital stay [24], but all these studies were done in well-resourced settings, including round the clock availability of endotracheal intubation and mechanical ventilation. In the current study none of these potential benefits of early enteral feeding could be detected.…”
Section: Discussionmentioning
confidence: 99%
“…The total calorie goal was 20 to 25 kcal/kg in the acute phase of injury and 25 to 30 kcal/kg during I nadequate intake of calories and protein is a common problem in intensive care units (ICUs) [1][2][3][4] and results from a combination of a hypercatabolic state and a reduction in the nutrient supply. 5,6 The reduced nutrient supply may be due to an underestimation of the amount of calories and protein needed [7][8][9][10] or to the difference between the number of calories prescribed and the number received. The percentage of prescribed calories that is actually received varies between 51% and 99%.…”
Section: Methodsmentioning
confidence: 99%